Development of Garcinia atroviridis capsule towards safe, quality and efficacious product - MN Noor Rasyila, MS Zamree, MH Nurhazwani, MA Nor Azah, AL Tan, Y Norulaiman, R Adib Zubaidi, A Mohd Hafidz Hadi, A Mohd Faizal, M Juliza, S Rohana (Universiti Pendidikan Sultan Idris, 2017)
Development of Garcinia atroviridis capsule towards safe, quality and efficacious product by MN Noor Rasyila, MS Zamree, MH Nurhazwani, MA Nor Azah, AL Tan, Y Norulaiman, R Adib Zubaidi, A Mohd Hafidz Hadi, A Mohd Faizal, M Juliza, S Rohana,